Beta-Adrenergic Blockade in Critical Illness - Bruning, Rebecca; Dykes, Hannah; Jones, Timothy W.; Wayne, Nathaniel B.; Sikora Newsome, Andrea (Frontiers in Pharmacology, 2021)
Catecholamine upregulation is a core pathophysiological feature in critical illness. Sustained catecholamine β-adrenergic induction produces adverse effects relevant to critical illness management. β-blockers (βB) have proposed roles in various critically ill disease states, including sepsis, trauma, burns, and cardiac arrest. Mounting evidence suggests βB improve hemodynamic and metabolic parameters culminating in decreased burn healing time, reduced mortality in traumatic brain injury, and improved neurologic outcomes following cardiac arrest. In sepsis, βB appear hemodynamically benign after acute resuscitation and may augment cardiac function. The emergence of ultra-rapid βB provides new territory for βB, and early data suggest significant improvements in mitigating atrial fibrillation in persistently tachycardic septic patients. This review summarizes the evidence regarding the pharmacotherapeutic role of βB on relevant pathophysiology and clinical outcomes in various types of critical illness.